The Relation of Baseline Serum Albumin with the Duration of Neutropenia after Induction Chemotherapy in Adult Acute Leukaemia - Nadeem, Muhammad; Khan, Nayab; Piracha, Muhammad Khalid; Majeed, Farhan Ahmed; Halim, Ayesha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the relation of baseline serum albumin levels with the duration of neutropenia after induction chemotherapy in acute leukaemia.Study design: Prospective longitudinal study.Place and Duration of Study: Department of Medical Oncology, Combined Military Hospital, Rawalpindi Pakistan, Dec 2018 and Dec 2020.Methodology: Ninety-one patients with newly diagnosed acute leukaemia who were planned to receive induction chemotherapy were included. Before starting chemotherapy, blood counts and serum albumin levels were determined in each patient. The tests were monitored during treatment, and the duration of days when the patient experienced neutropenia was noted. Results: The mean age of participants was 29.70±9.50 years. 64(70.3%) were males and 27(29.7 %) were female. At presentation, the mean white blood cell (WBC) count in peripheral blood was 16.70±39.60 x109/L. 29 (31.9%) patients had hypoalbuminemia with serum albumin